PENILE CANCER AND MULTIPLE PREPUTIAL STONE: A RARE CASE REPORT - Munawwir, Abdul; Yonatha, Teddy (Indonesian Journal of Urology, 2025)
Objective: This paper aims to report a case of penile cancer with multiple prepuce stones in a 46-year-old non-circumcised male. Case Presentation: A 46-year-old male patient came to the clinic with complaints of a slowly enlarging penis since the last 2 months. Complaints are accompanied by difficulty and pain when urinating, sometimes there are stones that come out when urinating. Physical examination revealed an enlarged penis, irregular shape, tenderness, unclear borders. Multiple prepuce stones, pus accumulation, and suspicion of malignancy in the penis were observed. Histopathology showed squamous cell carcinoma (SCC) of the penis. The patient was discharged 4 days postoperatively and prepared for follow-up treatment. Discussion: Penile cancer and prepuce stones are very rare cases. Smegma accumulation, chronic inflammation, and urinary stasis are the pathophysiology of penile cancer and prepuce stones. Conclusion: Penile cancer and preputial stones are very rare. We performed a surgical procedure to divert urine by urethral catheterisation, treated the infection and took penile tissue for biopsy, after which he was referred for further treatment. Keywords: Penile cancer, multiple prepuce stone, a rare case report.